Characterization of Vietnamese Lacquer Collected in Different Seasons - Rong Lu; Kenichiro Anzai; Bach Trong Phuc; Tetsuo Miyakoshi (International Journal of Polymer Science)
Vietnamese lacquers collected every month from June to March of next year were characterized. Composition analysis showed that lacquer collected in rainy season contained much water, while those collected in dry season contained more lipid component. Although hardness of lacquer films is not very hard, lacquers tapped in all seasons can reach hard dry (HD) within 48 hours. Refining lacquer can accelerate drying time but the water concentration should be maintained around 10 wt% for laccase activity.